2020
DOI: 10.48550/arxiv.2008.06531
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Average Order of Dominating Sets of a Graph

Abstract: This papers focuses on the average order of dominating sets of a graph. We find the extremal graphs for the maximum and minimum value over all graphs on n vertices, while for trees we prove that the star minimizes the average order of dominating sets. We prove the average order of dominating sets in graphs without isolated vertices is at most 3n/4, but provide evidence that the actual upper bound is 2n/3. Finally, we show that the normalized average, while dense in [1/2, 1], tends to 1 2 for almost all graphs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Our focus in this paper will be on the average order of a dominating set of a graph. A subset of vertices S is called a dominating set of G if every vertex in V (G) \ S is adjacent to some vertex in S. Let D(G) denote the family of all dominating sets of G. Recently Beaton and Brown [4] introduced the average order of a dominating set of G, denoted avd(G), which is given by…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our focus in this paper will be on the average order of a dominating set of a graph. A subset of vertices S is called a dominating set of G if every vertex in V (G) \ S is adjacent to some vertex in S. Let D(G) denote the family of all dominating sets of G. Recently Beaton and Brown [4] introduced the average order of a dominating set of G, denoted avd(G), which is given by…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the complete graph K n uniquely minimizes the average order of a dominating set among all graphs on n vertices [4]. It is trivial that…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations